New or poorly known Microlepidoptera from the Mascarenes (Lepidoptera: Autostichidae, Bedellidae, Batrachedridae, Carposinidae, Eperminiidae, Gelechiidae, Tineidae, Tortricidae). - Bippus, Maik (Contributions to Entomology = Beiträge zur Entomologie, 2016)
Peragrarchis martirea (Carposinidae), Epermenia senaciae (Epermeniidae), Opogona transversata and Tineovertex flavilineata (Tineidae) are described as new species, and Idioglossa bigemma mascarena (Batrachedridae) as a new subspecies, from the Mascarene island of La Réunion, and Mauritius. Eleven species are new for the fauna of La Réunion, two are new for the fauna of Mauritius. New host plants are reported for twelve species. Opogona reunionella Guillermet, 2011 was found to be a new synonym of Opogona siccata (Meyrick, 1910), based on the study of type material and additional specimens.KeywordsLepidoptera, Autostichidae, Bedellidae, Batrachedridae, Carposinidae, Epermeniidae, Gelechiidae, Tineidae, Tortricidae, Mascarenes, taxonomy, new species, new synonym, additional records.Nomenclatural Actssenaciae Bippus, 2016 (Epermenia), spec. nov.bigemma mascarena Bippus, 2016 (Idioglossa), sspec. nov.transversata Bippus, 2016 (Opogona), spec. nov.martirea Bippus, 2016 (Peragrarchis), spec. nov.flavilineata Bippus, 2016 (Tineovertex), spec. nov.